'Treatment or diagnosis - a study of repeat prescriptions in general practice'. Issue 16 (30th July 1971) - Unknown
Abstract : This book, the latest in the Mind and Medicine series of monographs, was published shortly before the death of Michael Balint, who edited and inspired the series. It grew out of the work of a Training-cum-Research Seminar of general practitioners that he led. Its messages are important for all doctors, not only for those in general practice.